Genome‐wide association study of height‐adjusted BMI in childhood identifies functional variant in ADCY3. (21st July 2014) - Stergiakouli, Evangelia; Gaillard, Romy; Tavaré, Jeremy M.; Balthasar, Nina; Loos, Ruth J.; Taal, Hendrik R.; Evans, David M.; Rivadeneira, Fernando; St Pourcain, Beate; Uitterlinden, André G.; Kemp, John P.; Hofman, Albert; et al.
<x xml:space="preserve">Abstract</x> Objective Genome‐wide association studies (GWAS) of BMI are mostly undertaken under the assumption that "kg/m2" is an index of weight fully adjusted for height, but in general this is not true. The aim here was to assess the contribution of common genetic variation to a adjusted version of that phenotype which appropriately accounts for covariation in height in children. Methods A GWAS of height‐adjusted BMI (BMI[x] = weight/heightx), calculated to be uncorrelated with height, in 5809 participants (mean age 9.9 years) from the Avon Longitudinal Study of Parents and Children (ALSPAC) was performed. Results GWAS based on BMI[x] yielded marked differences in genomewide results profile. SNPs in ADCY3 (adenylate cyclase 3) were associated at genome‐wide significance level (rs11676272 (0.28 kg/m3.1 change per allele G (0.19, 0.38), P = 6 × 10−9). In contrast, they showed marginal evidence of association with conventional BMI [rs11676272 (0.25 kg/m2 (0.15, 0.35), P = 6 × 10−7)]. Results were replicated in an independent sample, the Generation R study. Conclusions Analysis of BMI[x] showed differences to that of conventional BMI. The association signal at ADCY3 appeared to be driven by a missense variant and it was strongly correlated with expression of this gene. Our work highlights the importance of well understood phenotype use (and the danger of convention) in characterising genetic contributions to complex traits.